Scaling up DNA barcoding – Primer sets for simple and cost efficient arthropod systematics by multiplex PCR and Illumina amplicon sequencing. Issue 11 (3rd August 2018) - Krehenwinkel, Henrik; Kennedy, Susan R.; Rueda, Alexandra; Lam, Athena; Gillespie, Rosemary G.
Abstract: The simplicity and cost efficiency of Illumina amplicon sequencing has greatly contributed to the advancement of DNA barcoding and metabarcoding applications. However, current amplicon sequencing‐based barcoding approaches are usually restricted to short, single‐locus fragments, limiting their taxonomic and phylogenetic resolution. Here, we establish a cost efficient and simple multiplex PCR protocol for arthropod systematics by Illumina amplicon sequencing. We introduce primer sets, including several new, generic primers, to reliably amplify nine loci across a wide range of arthropods. Using a diverse collection of arthropod species from 19 orders, we test loci for amplification efficiency and estimate the effect of cross‐species amplification bias on taxon recovery from bulk community samples. We then explore the taxonomic and phylogenetic utility of the primer sets, focusing on a dataset of spiders that includes both deep and recent divergences. The set of loci provides good phylogenetic support across a wide taxonomic spectrum, making it a useful addition to COI for resolving lineages within a comparative context. All loci recover sequences for the majority of arthropod taxa in separate PCRs. However, cross‐species amplification bias in some primers prevents an exhaustive taxon recovery from bulk community samples. Our protocol makes it possible to generate multilocus datasets for large numbers of arthropod taxa for a fraction of the price and workload of Sanger sequencing. This opens up the possibility for parallel phylogenetic and taxonomic analysis of large collections of arthropods, but also enables rapid exploratory analyses of target lineages. Primers for metabarcoding applications should be carefully evaluated for their performance in bulk community samples and chosen to minimize cross‐species amplification bias.